Effect of Ramadan fasting on some aspects of exercise performance in Iranian athletes - Siemensma, A. D.; Calame, W. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. I, 2008)
Background: The aim of this study was to measure the effects of a month of Ramadan fasting on blood biochemical factors and some aspects of exercise performance in Iranian athletes. 34 male athletes (Mean ±SD age 21± 4 y, height 177± 9 cm, body mass 76.5±15.3 kg) participated in three different groups:1.weight category sports N=12; 2. non-weight category sports N=11; 3. physically active persons N=11. Subjects were tested on four different sessions: 1= one week before Ramadan; 2= one week after the start of fasting; 3= during the last week of Ramadan; 4= one week after the end of Ramadan. Urine and blood sample were collected before body mass, body fat, by skin fold thickness, and body water content were measured. A series of Eurofit tests were then completed. Most of the measured factors significantly changed during the month of Ramadan, but most returned to baseline one week after Ramadan. Body mass, sum of skin folds, and body fat percentage, fell progressively during Ramadan and returned to pre-Ramadan levels afterwards (p=0.01).There was a significant correlation between the change in body mass and the change in body fat (p=0.01). Performance in the Sit up, Long jump and Endurance shuttle run tests was lower during fasting (trial2 and 3) vs fed sessions (1 and 4; p=0.01). 3×20 m shuttle run test performance generally decreased amongst groups and did not recover even after a week of the end of Ramadan (p=0.01). There was no difference between groups in the pattern of changes over time. Conclusions Ramadan style life, involving a change in timing of food intake and sleep pattern, affects most of the anthropometric and physical performance characteristics of athletes and physically active non-athletes. However, most parameters recovered a week after the end of Ramadan. The level of physical activity seems to have no effects on the pattern of performance changes.